Survey of Students Satisfaction and Some Efforts to Improve Lecturer Profesionalism in the English Education Department of STKIP Situs Banten - Salim, Herli; Septiana, Tri Ilma (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims to determine the level of student satisfaction with the performance of lecturers, especially in the lecture processes and academic services; and examine the efforts that made by STKIP Situs Banten in improving the professionalism of lecturers. The study used descriptive qualitative method with data collection techniques through questionnaires, document analysis, literature study, and interviews. Data were obtained from the questionnaire was processed using the IBM SPSS Statistics 21 application which was then interpreted descriptively. Meanwhile, the data obtained from the analysis of documents, literature studies, and interviews were analyzed using the interactive model of Milles and Huberman, namely data collection, data reduction, data presentations, and conclusions. The results of this study indicate that overall students feel very satisfied in academic services, this shows that the performance of lecturers can be categorized very well. In addition, some efforts to improve the professionalism of lecturers can be done by developing pedagogical competencies, information engineering competencies, management / administrative competencies, curriculum competencies, scientific competencies (research and publications), evaluation competencies; and personal competence.